2020
DOI: 10.1128/mbio.01364-20
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Surface Carbohydrates in Bacterial Pathogens Requires Coordinated Action of a Two-Domain Membrane-Bound Acyltransferase

Abstract: Membrane bound acyltransferase-3 (AT3) domain-containing proteins are implicated in a wide range of carbohydrate O-acyl modifications, but their mechanism of action is largely unknown. O-antigen acetylation by AT3 domain-containing acetyltransferases of Salmonella spp. can generate a specific immune response upon infection and can influence bacteriophage interactions. This study integrates in situ and in vitro functional analyses of two of these proteins, OafA and OafB (formerly F2GtrC), which display an “AT3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(85 citation statements)
references
References 106 publications
(137 reference statements)
2
83
0
Order By: Relevance
“…Deletion of atf3 does not alter the physical properties of KP35 Neither the primary sequence nor the predicted protein structure of the KP35 atf3 gene product indicates its function. However, atf3 is colocated with multiple genes involved in capsular production (ugd, gnd; components of the cps cluster in K. pneumoniae) (Pan et al, 2015) and O-antigen synthesis (wbgU, tagGH) (Bruchmann et al, 2021;Caboni et al, 2015) (Figure 2A). To study the role of atf3 in pathogenesis, a null mutant was constructed using a recently adapted CRISPR-Cas9 system, Lambda Red Recombineering genes to improve efficiency, and Zeocin selection due to the presence of multiple antimicrobial resistance elements in the KP35 genome (McConville et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of atf3 does not alter the physical properties of KP35 Neither the primary sequence nor the predicted protein structure of the KP35 atf3 gene product indicates its function. However, atf3 is colocated with multiple genes involved in capsular production (ugd, gnd; components of the cps cluster in K. pneumoniae) (Pan et al, 2015) and O-antigen synthesis (wbgU, tagGH) (Bruchmann et al, 2021;Caboni et al, 2015) (Figure 2A). To study the role of atf3 in pathogenesis, a null mutant was constructed using a recently adapted CRISPR-Cas9 system, Lambda Red Recombineering genes to improve efficiency, and Zeocin selection due to the presence of multiple antimicrobial resistance elements in the KP35 genome (McConville et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous bacterial acyltransferases with diverse functions (Rö ttig and Steinb€ uchel, 2013) and >60 independent proteins identified as targets for acylation (Hentchel and Escalante-Semerena, 2015). Members of the acyltransferase superfamily 3, of which atf3 of KP35 belongs, are present in prokaryotes and eukaryotes, with enrichment of matching orthologous sequences across Gammaproteobacteria, a class of bacteria to which K. pneumoniae belongs (Pearson et al, 2020). A notable member of this family includes OatA, an enzyme that O-acetylates the peptidoglycan of Staphylococcus aureus, leaving it resistant to lysozyme degradation (Bera et al, 2006;Herbert et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although having known O-acetylesterase activity, the SGNH domain is essential for the acyltransferase activity of AT3-SGNH fused carbohydrate acyltransferases [4,11,29,30] (Fig. 1).…”
Section: Architecture Of At3 Proteinsmentioning
confidence: 99%
“…Elevated levels of LPS can be detected in the plasma of humans showing features of metabolic syndrome, including obesity, insulin resistance, dyslipidemia, and chronic low-grade inflammation [ 166 ], which is exacerbated upon high fat intake [ 167 ]. Still, as LPS is a complex molecule found in different acetylation forms affecting molecular structure [ 168 ] and thereby binding capacity, not all types of LPS are metabolically detrimental to the host. Comparing the metabolic effects of Escherichia coli -derived and Rhodobacter sphaeroides -derived LPS, it was recently demonstrated that only E. coli LPS mediated intestinal barrier disruption, dysglycemia, and low-grade inflammation of adipose tissue [ 169 ].…”
Section: Bacterial Translocation As a Function Of Diet-induced Barrie...mentioning
confidence: 99%